Heat distribution concepts for small solar district heating systems – Techno-economic study for low line heat densities. (August 2022) - Andersen, Martin; Bales, Chris; Dalenbäck, Jan-Olof
Highlights: Two novel distribution concepts are compared to conventional district heating. A novel distribution system with central domestic hot-water heating is presented. Hybrid distribution outperforms a conventional steel pipe system. A complete low-temperature system outperforms hybrid distribution. Reduction in line heat density favours a low-temperature GRUDIS system. Abstract: The high operating temperatures in today's district heating networks combined with the low energy demand of new buildings lead to high relative network heat losses. New networks featuring lower operating temperatures have reduced relative heat losses while enabling an increase in the use of solar heat. The primary aim of this study was to determine if a particular district heating system can be made more effective with respect to heat losses and useful solar energy, by considering different distribution concepts and load densities. A small solar assisted district heating system with a novel hybrid distribution system has been modelled based on a real case study. This model serves as a basis for two other models where the distribution system and heating network operating temperature is changed. A secondary aim of the study was to determine the economic implications of making these changes, by using costs estimates to calculate the contribution of essential system components to total system cost. Results indicate that a novel distribution concept with lower network temperatures and central domestic hot water preparation is most energy efficient in a sparse network with a heat density of 0.2 MWh/m∙a and a performance ratio of 66%, while a conventional district heating system performs worst and has a performance ratio of less than 58% at the same heat density. In an extremely sparse network with heat density of 0.05 MWh/m∙a, the performance ratio is 41% and 30% for these systems, respectively. A simple economic analysis indicates that the novel distribution concept is also best from an economic point of view, reducing the initial investment cost by 1/3 compared to the conventional concept, which is the most costly. However, more detailed calculations are needed to conclude on this.